Heidegger on Gaining a Free Relation to Technology (Tábano, 2024)
According to Hubert L. Dreyfus, Heidegger was not concerned with the problem of human control of technology that preoccupies the technology-as-ideology theorists. In his text, Dreyfus argues that the issue is rather the understanding of being as mere raw material projected in the technological worldview of the modern West. Only by realizing that being itself commands this dispensation can we begin to distance ourselves from that worldview. Ultimately, technology is not a political matter but a mode of givenness specific to the modern age. This realization places us beyond a purely technological outlook on life and opens us to a different relation to technology. What is needed is a new sense of reality that privileges the non-technological facets of experience and community. In that context, technology would continue to exist and do its work but would no longer form the horizon of being and understanding.
Keywords: Heidegger; Technology; Danger; Clearing; Relation